A cluster randomised controlled trial on the efficacy of client-centred occupational therapy in multiple sclerosis: good process, poor outcome. (September 2013) - Eyssen, Isaline C. J. M.; Steultjens, Martijn P. M.; de Groot, Vincent; Steultjens, Esther M. J.; Knol, Dirk L.; Polman, Chris H.; Dekker, Joost
Abstract Purpose: To assess the efficacy of client-centred occupational therapy (OT) according to a client-centred process framework, as compared to usual care OT, in patients with multiple sclerosis (MS). Method: A multicentre cluster randomised controlled trial with the institution (i.e. hospital or rehabilitation centre) as the unit of randomisation was performed. A total of 269 outpatients with MS, 13 hospitals and rehabilitation centres and 29 occupational therapists participated. Primary outcomes included measures of disability, participation and autonomy. Secondary outcomes included fatigue, generic health-related quality of life, quality and evaluation of therapy, therapy compliance and therapy frequency. Measurements were taken at baseline, four months and at eight months follow-up. Results: Primary outcome measures did not show significant differences between the two interventions. Secondary outcomes revealed significant differences in favour of the usual care OT on fatigue (physical scale and total scale) and health-related quality of life (bodily pain and vitality) at four months. After eight months only significant differences on mental health were found. Process outcomes (i.e. the information scale of therapy quality and the client-centredness of the organisation) were in favour of the client-centred intervention. Conclusion: Because the client-centred intervention resulted in no effects on the primary outcomes and small but negative effects on the secondary functional outcomes, we should seriously reconsider the application of client-centred practice. Implications for Rehabilitation An increasing number of interventions claim to incorporate client-centred practice. Client-centred practice is associated with improved satisfaction but the effects on functional health-related outcomes have not been fully evaluated. The findings of this study show that the process outcomes of therapy were in favour of the client-centred intervention, but no effects were found on the primary outcomes and negative effects on the secondary functional health outcomes. It is suggested that the implementation of client-centred practice should be adjusted in order to achieve optimal health outcomes.